2020
DOI: 10.1039/d0ob01790f
|View full text |Cite
|
Sign up to set email alerts
|

FeCl3-catalyzed oxidative decarboxylation of aryl/heteroaryl acetic acids: preparation of selected API impurities

Abstract: There is an ever-increasing demand for impurities required for profiling as regulatory agencies seek information during registration. Herein, we report FeCl3-catalyzed oxidative decarboxylation of aryl-, and heteroaryl acetic acids to...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…The 13 C NMR spectrum shows the C6-carbonyl group at δ 207.0 ppm, and the IR spectrum shows it at ν 1695 cm –1 . Compound 48 likely forms from C–H group oxidation at C6 followed by decarboxylative fragmentation to give the ketone function . No oxidation of the alkene function was found, and the oxidation reaction taking place at C6 of 46 , adjacent to the electron-withdrawing group, carboxylic acid, was unusual.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The 13 C NMR spectrum shows the C6-carbonyl group at δ 207.0 ppm, and the IR spectrum shows it at ν 1695 cm –1 . Compound 48 likely forms from C–H group oxidation at C6 followed by decarboxylative fragmentation to give the ketone function . No oxidation of the alkene function was found, and the oxidation reaction taking place at C6 of 46 , adjacent to the electron-withdrawing group, carboxylic acid, was unusual.…”
Section: Resultsmentioning
confidence: 99%
“…No oxidation of the alkene function was found, and the oxidation reaction taking place at C6 of 46 , adjacent to the electron-withdrawing group, carboxylic acid, was unusual. Moreover, the C–H group oxidation of cyclic aryl-α-carboxylic acid followed by decarboxylative fragmentation to form the corresponding ketone is a useful process such as ensuring the quality of active pharmaceutical ingredients . Functional group manipulations of 47 and 48 will provide a library of novel derivatives for drug discovery screening .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Carboxylic acids, ubiquitous in biomass sources and industrial feedstocks, are among the most attractive functional groups in organic synthesis. In this context, carboxylic acids and their activated derivatives readily undergo a diverse range of decarboxylative transformations to form carbon–carbon, carbon–halogen, and other carbon–heteroatom bonds. In contrast, their decarboxylation and subsequent CO double-bond formation have been rarely explored and only very few papers have been reported to date, typically limited to benzylic carboxylic acids (Scheme A). Recently, Hosseini-Sarvari demonstrated that carboxylic acids could be converted efficiently to carbonyl-containing compounds including aldehydes and ketones using a Au@ZnO photoredox catalyst (Scheme B) . At almost the same time, MacMillan group disclosed an elegant decarboxylative oxygenation method providing aldehydes, ketones, and amides from readily available carboxylic acids via iridium photoredox catalysis .…”
Section: Introductionmentioning
confidence: 99%